Managing the Interest Rate Risk of Indian Banks' Government Securities Holdings - Sy, Amadou (Washington, D.C. : International Monetary Fund, 2005)
The large holdings of government securities by banks in India draw attention to their risk as interest rates are at historical low levels. This paper measures such a risk using duration and value-at-risk methods and assesses its current management by banks. The main finding is that some public sector and old private banks are vulnerable to a reversal of the interest rate cycle, while foreign and new private banks have built adequate defenses. In this regard, the paper makes a number of recommendations regarding government policies and individual bank practices to manage interest rate risk.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet